Is sheltered employment more stable than ordinary employment? - Cuetoa, Begoña; Rodriguez, Vanesa (Work, 2016)
BACKGROUND: Sheltered Employment Centres are a key component of policies promoting the employment of people with disabilities in Spain. The firms involved form a sort of 'protected' labour market for people with disabilities. Their purpose is to provide employment opportunities for people with disabilities who have difficulties entering the 'ordinary' labour market. OBJECTIVE: The aim in this article is to analyse whether workers with disabilities enjoy greater stability in sheltered employment centres than in ordinary firms. METHODS: Using data from the Longitudinal Sample of Working Lives, which includes information about the labour market trajectory of Spanish workers, survival models are employed to analyse the duration of employment periods of workers with disabilities. Workers in sheltered employment centres are compared to workers in ordinary firms. RESULTS: Results confirm that employment in SECs is more stable than in ordinary firms, even after controlling for the effects of other variables such as sex, age, level of qualifications and characteristics of the firms. CONCLUSIONS: Employment in SEC provides to workers with disability a more stable career path with lower turnover than working in ordinary firms. More research is needed to consider other working conditions such as wages and promotion possibilities.